Targeting T-Cell Activation for Malaria Immunotherapy: Scoping Review - Balsa Nobility Gustifante; Shafia Khairani; Nisa Fauziah; Silvita Fitri Riswari; Afiat Berbudi (Pathogens)
Malaria remains a critical global health issue due to high mortality rates, drug resistance, and low treatment efficacy. The genetic variability of Plasmodium proteins complicates the development of long-lasting immunity, as it impedes the human immune system’s ability to sustain effective responses. T cells play a crucial role in combating malaria, but the parasite’s complex life cycle—spanning liver and blood stages—presents significant challenges in effectively activating and targeting these cells. Immunotherapy, which enhances the immune response and promotes durable T cell activity, offers a promising avenue for more effective and lasting malaria treatments. This review systematically analyzed 63 studies published in the last decade, focusing on the role of T cells in malaria. Among the studies, 87.2% targeted T cells as immunotherapy candidates, with CD4+ and CD8+ T cells each accounting for 47.6% of the studies. γδ T cells were the focus in 7.9% of cases, while 12.7% explored non-T cell contributions to enhancing T cell-mediated responses. The findings underscore the potential of T cells, particularly CD8+ T cells, in liver-stage defense and advocate for the exploration of advanced vaccine platforms and novel therapies, such as mRNA-based vectors and monoclonal antibodies.